Fixing a fractured arthrodesed hip with rapid prototype templating and minimal invasive plate osteosynthesis - Christian Fang; Benjamin Fang; Tak-Man Wong; Tak-Wing Lau; Terence Pun; Frankie Leung (Trauma Case Reports, 2015)
CASE:: We present an elderly lady with an intertrochanteric fracture of a previously fused hip. A 3D printed model of her pelvis and femur was used for implant templating before surgery. Minimal invasive fixation was performed with a spanning reversed distal femur locking plate without the need for removal of the previous implant. Multiple long locking screws were placed in the supra-acetabular region. The patient had union in 4 months, return to function and no complication. Conclusion:: The technique allowed us to optimize implant selection and insert screws safely at difficult trajectories using minimal invasive surgery. Keywords: Hip fusion, Fracture, Plating, Minimal invasive, 3D printing